Penyalahgunaan Kewenangan Oleh Pejabat Pemerintah Dalam Pasal 10 Ayat (1) Huruf E Undang-Undang Nomor 30 Tahun 2014 Tentang Administrasi Pemerintahan - Resti Khairunnisa Fitri; Dian Pertiwi (UIN Mahmud Yunus Batusangkar, 2023)
This study examines the abuse of authority committed by Government Offficials, in this case the Head of the Koperindag Office of Tanah Datar Regency for the 2019 period, from the problem the question arises, namely the forms of abuse of authority committed by the former Head of the Koperindag Office of Tanah Datar Regency for the 2019 period in Article 10 Paragraph (1) Letter e of Law Number 30 of 2014, what is Siyasah DusturiyahÔÇÖs view of Government Officials who abuse their authority. This research is a library research. The secondary data sources the researchers took from Law Number 30 of 2014 concerning Government Administration and books related to research by researches. The researchÔÇÖ primary legal materials are the result of research, books, papers, journals, the internet and other written sources. The result of the research that the authors obtained were that the former Head of the Koperindag Service Office of Tanah Datar Regency for the 2019 period┬áallegedly violated Article 10 Paragraph (1) Letter e of Law Number 30 of 2014 because he had abused his authority in this case based on the source of attribution authority regarding the bribery case with a contractor for the X Koto market development project, Tanah Datar Regency. According to Siyasah Dusturiyah, government officials fall within the scope of Wizarah Tanfidz. Islam prohibits abuse of authority by government officials because Allah curses bribers and those who are bribed in matters of law. The word of the Prophet SAW ┘ä Ï®┘åÏ╣ ┘êÏº Ï┤Ï¬Ï▒┘à┘ä Ïº Ï┤ÏºÏ▒┘ä ┘ä ┘Ä ÔùîÏ╣ ┘ä┘ä┘æ ┘Ä ÔùîÏº ÔÇØ AllahÔÇÖs curse on the bribegiver and bribe-takerÔÇØ